Адаптація безпроводової сенсорної мережі в умовах складної електромагнітної сумісності радіоелектронних засобів полігону - Куля, Ю. Е.; Шостко, І. С. (ХНУРЕ, 2019)
In the case of simultaneous operation of the wireless sensor network and other wireless telecommunication systems (TCS) or electronic means (REMs) focused on the territory of the polygon and using the same frequency resource of 2.4 GHz, it is necessary to solve the problem of electromagnetic compatibility (EMC) taking into account the limits of the range Radio communication for individual nodes of the c (IMS)
Keywords: безпроводова сенсорна мережа; АРПr; АРПt; ЕМС